Molecular Identification of Yeasts and Lactic Acid Bacteria Involved in the Production of Beninese Fermented Food Degue - Angelov, Angel I.; Petrova, Galya; Angelov, Angel D.; Stefanova, Petya; Bokossa Y., Innocent; TCHEKESSI, C. K. Célestin; Marco, Maria L.; Gotcheva, Velitchka (My University, 2017)
Abstract: Background: Traditional Beninese fermented food Degue is widely consumed in Benin and other countries in West Africa. It was originally made from milk and millet flour, but currently other cereals are used as well. Nowadays, Degue production occurs by spontaneous fermentation in individual households and information about the microorganisms involved is currently limited. Objective: The microbiota of Degue from Benin has not been studied so far, but its growing production in the country sets a demand for revealing the biodiversity of the microbial population involved in the fermentation process in order to take future steps for development of industrial technology and offer products with improved quality and safety. Method: In the present study, yeast and lactic acid bacteria from raw materials for Degue production and from several Degue products were isolated and identified by molecular methods including RFLP and ITS1-5.8S-ITS2 rRNA gene sequence analysis in yeasts, and 16S rRNA gene sequence analysis in lactic acid bacteria. Results: Lactic acid bacteria isolates were assigned to eight species within the genera Lactobacillus, Enterococcus, Pediococcus, Streptococcus and Weisella. Four species of yeasts were found in Degue: Cyberlyndnera fabianii, Candida glabrata, Kluyveromyces marxianus, and Meyerozyma caribbica. Conclusion: The microbial population revealed is unique to Beninese Degue and needs further characterization for development of defined starter cultures.
Keywords: Degue; Benin; Identification; Yeast; Lactic acid bacteria; Molecular methods.